Documenting Reading Achievement and Growth for Students Taking Alternate Assessments. (April 2016) - Tindal, Gerald; Nese, Joseph F. T.; Farley, Dan; Saven, Jessica L.; Elliott, Stephen N.
Students with disabilities have been included in state accountability systems for more than a decade; however, only in the past few years have alternate assessments of alternate achievement standards (AA-AAS) become stable enough to allow examination of these students' achievement growth. Using data from Oregon's AA-AAS in Reading during the period 2008–2009 to 2010–2011, we examined the achievement growth for a sample of 1, 061 elementary students using two growth models: a transition matrix and a multilevel linear growth model. The authors found with the transition matrix model that a majority of students remained at the same performance level from one year to the next, whereas with the multilevel linear growth model, students' scores revealed small, but statistically meaningful, growth year to year. The article concludes by noting advantages and disadvantages of these models to characterize growth and their implications for policy and practice.